(untitled) (Applied Biological Research, 2020)
The present study was conducted on 31 genotypes of spine gourd (Momordica dioica Roxb.) to estimate genetic variability, correlation and path coefficient analysis. The high estimates of PCV for the number of stem plant-1(21.47) and moderate GCV and PCV observed for most of the traits which indicated the presence of adequate genetic variation among the genotypes. High heritability estimates coupled with high genetic advance for the number of fruits plant-1 and fruit yield confirmed that these traits are under the control of additive gene action. Fruit yield showed significant positive association with days to first flowering, number of stems plant-1, fruit weight and number of fruits plant-1. The higher association of number of fruits plant-1, number of stem plant-1, days to first flowering, fruit weight, fruit diameter and ovary diameter may be attributed to their direct effect on fruit yield. The study showed that the selection of traits with high positive significant association and high positive direct effect on fruit yield can help in improving yield. The similarity coefficient ranged from 0.33 to 0.94. In pair-wise comparison, the maximum similarity was obtained between genotype with a similarity index of 0.32 to 0.50, whereas genotype showed least similarity with other genotypes.